ChemInform Abstract: Beyond Directing Groups: Transition‐Metal‐Catalyzed C—H Activation of Simple Arenes. Issue 10 (7th March 2013) - Kuhl, Nadine; Hopkinson, Matthew N.; Wencel‐Delord, Joanna; Glorius, Frank
Abstract Review: ca. 300 refs.